The relationship between overnight GH levels and insulin concentrations in adolescents with insulin-dependent diabetes mellitus (IDDM) and the impact of recombinant human insulin-like growth factor I (rhIGF-I). - Cheetham, T; Connors, M; Clayton, K; Watts, A; Dunger, D (1997)
OBJECTIVE: We examined the relationship between GH concentrations and free insulin concentrations, used as an index of insulin sensitivity, before and after recombinant human insulin-like growth factor I (RhIGF-I) administration in adolescents with insulin-dependent diabetes mellitus (IDDM). DESIGN AND PATIENTS: Growth hormone concentrations were assessed by a peak detection programme (Pulsar) on a control night (2000 h-0800 h) and a night when rhIGF-I administered in a subcutaneous dose of 40 micrograms/kg at 1800 h to 16 adolescent subjects. Stable euglycaemia was maintained by a continuous intravenous insulin infusion and changes in free insulin levels on the two nights were compared with growth hormone data. RESULTS: Mean overnight GH concentrations (2000 h-0800 h) on the control night were positively related to glycated haemoglobin (Hba1) concentrations (r = 0.63; P < 0.01) and were reduced following rhIGF-I administration (24.9 +/- 3.6 mU/I on the control night versus 17.4 +/- 2.2 mU/I after administration, P = 0.01). The mean GH pulse amplitude on the control night was related to the change in GH levels after rhIGF-I (rs = -0.66, P < 0.001). Multiple regression analysis revealed that mean GH pulse amplitude was the only determinant of free insulin concentrations (0500 h-0700 h on both study nights (P < 0.01). The percentage change in mean growth hormone pulse amplitude between the two nights was related to the percentage reduction in free insulin concentrations (r = 0.53, P = 0.03). CONCLUSIONS: Growth hormone pulse amplitude is related to early morning insulin sensitivity in adolescents with IDDM on control nights and after rhIGF-I administration. The reduction in insulin levels following rhIGF-I may be linked to the change in GH pulse amplitude and not just to direct insulin-like actions. Individuals with the higher GH (and thus HbA1 levels) were most sensitive to the GH-suppressive effects of rhIGF-I.